Determinants of Awareness of Workplace Accident Reporting at the Technical Implementation Unit of Madani General Hospital in Palu - Regieta Gienanti Y. Lalusu; Budiman Budiman; Finta Amalinda (PROMOTOR, 2026)
Occupational Health and Safety (OHS) is an essential aspect of creating a safe working environment in hospitals. However, the reporting of occupational accidents remains suboptimal. This study aimed to analyze the determinants influencing awareness of occupational accident reporting at the Technical Implementation Unit of Madani General Hospital, Palu. Method: This research employed a quantitative method with a cross- sectional design. The study population consisted of all medical and non- medical health workers totaling 753 individuals, with a sample of 289 respondents selected using a random sampling technique. Data were collected using a Google Form–based questionnaire. Data analysis included univariate analysis, bivariate analysis using the Chi-Square test, and multivariate analysis using logistic regression. Result: The results showed a significant relationship between coworker support (p=0.000) and knowledge of OHS reporting procedures (p=0.000) with awareness of occupational accident reporting. Meanwhile, basic knowledge of OHS was not associated with reporting awareness (p=0.862). The variable of OHS training history could not be analyzed because all respondents (100%) had never attended OHS training. Multivariate analysis indicated that coworker support was the most dominant variable influencing awareness of occupational accident reporting, with an Exp(B) value of 68.178. Discussion: In conclusion, coworker support and knowledge of OHS reporting procedures significantly influence awareness of occupational accident reporting, with coworker support identified as the most dominant factor. Hospital management is recommended to enhance workplace support, strengthen the dissemination of OHS reporting procedures, and conduct regular OHS training to improve awareness of occupational accident reporting.